Neuronal current imaging: An experimental method to investigate electrical currents in dogs with idiopathic epilepsy. (8th October 2021) - Unger, Daniela M.; Wiest, Roland; Kiefer, Claus; Raillard, Mathieu; Dutil, Guillaume F.; Stein, Veronika M.; Schweizer, Daniela
Abstract: Background: The diagnosis of idiopathic epilepsy (IE) in dogs is based on exclusion of other potential causes of seizures. Recently, a novel magnetic resonance imaging (MRI) sequence that utilizes a variant of the rotary saturation approach has been suggested to detect weak transient magnetic field oscillations generated by neuronal currents in humans with epilepsy. Hypothesis/Objectives: Effects on the magnetic field evoked by intrinsic epileptic activity can be detected by MRI in the canine brain. As proof‐of‐concept, the novel MRI sequence to detect neuronal currents was applied in dogs. Animals: Twelve dogs with IE and 5 control dogs without a history of epileptic seizures were examined. Methods: Prospective case‐control study as proof‐of‐concept. All dogs underwent a clinical neurological examination, scalp electroencephalography, cerebrospinal fluid analysis, and MRI. The MRI examination included a spin‐locking (SL) experiment applying a low‐power on‐resonance radiofrequency pulse in a predefined frequency domain in the range of oscillations generated by the epileptogenic tissue. Results: In 11 of 12 dogs with IE, rotary saturation effects were detected by the MRI sequence. Four of 5 control dogs did not show rotary saturation effects. One control dog with a diagnosis of neuronal ceroid lipofuscinosis had SL‐related effects, but did not have epileptic seizures clinically. Conclusions and Clinical Importance: The proposed MRI method detected neuronal currents in dogs with epileptic seizures and represents a potential new line of research to investigate neuronal currents possibly related to IE in dogs.